2013
DOI: 10.1016/j.jhep.2013.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Impaired liver regeneration in Ldlr−/− mice is associated with an altered hepatic profile of cytokines, growth factors, and lipids

Abstract: Background & Aims It is widely recognized that in the early stages of liver regeneration after partial hepatectomy the hepatocytes accumulate a significant amount of lipids. The functional meaning of this transient steatosis and its effect on hepatocellular proliferation are not well defined. In addition, the basic mechanisms of this lipid accumulation are not well understood although some studies suggest the participation of the Low Density Lipoprotein Receptor (Ldlr). Methods To address these questions we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…These changes agreed with the temporal distribution of lipid droplets observed in Fig. A and are consistent with the concept that lipid droplets are lipid structures enriched in CEs and TGs . By contrast, the concentration of CE, TGs, and FFAs remained significantly lower in DLKO mice compared with WT mice, without major changes throughout the hepatic regeneration.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These changes agreed with the temporal distribution of lipid droplets observed in Fig. A and are consistent with the concept that lipid droplets are lipid structures enriched in CEs and TGs . By contrast, the concentration of CE, TGs, and FFAs remained significantly lower in DLKO mice compared with WT mice, without major changes throughout the hepatic regeneration.…”
Section: Resultssupporting
confidence: 90%
“…Early stages of liver regeneration are characterized by the formation of hepatocellular lipid droplets and changes in the hepatic lipidome. Several preclinical studies showed that alterations of these features impair hepatocellular proliferation during liver regeneration . To explore whether the hepatic loss of Akt may additionally affect lipid metabolism, we characterized both the hepatic lipid accumulation and the lipidomic profile of livers from WT, DLKO, and TLKO mice before and after PHx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For histological analysis, the upper right lobe was fixed in 4% neutral paraformaldehyde (PFA) at 4℃ and then cryoprotected overnight in 20% sucrose solution or embedded in Optimal Cutting Temperature medium for future processing. The percentage of liver regeneration was calculated following the formula: Percentage of liver regeneration = weight of non-removed lobes/total body weight of mice × 100% [23].…”
Section: Animal Surgerymentioning
confidence: 99%
“…Recently published reports add to this body of literature but do not yet resolve the question. For example, impairment of PH-induced liver regeneration associated with suppression of early hepatic fat accumulation was demonstrated in adipose differentiation related protein (Adrp)-KO- [35], tuberous sclerosis 2 (Tsc2)-haplo-insufficient- [36], and b-glucosylceramide-treated- [37] mice, and LDL-receptor null mice also exhibit delayed regeneration in association with alterations in the hepatic lipidome [38]. The latter finding suggests the interesting possibility that distinct alterations in hepatic lipidomic profiles, in different models in which PHinduced hepatic steatosis is disrupted, might account for the discrepant effects of disrupting hepatic fat accumulation on regeneration noted above and previously.…”
Section: Regenerative Hepatic Steatosismentioning
confidence: 99%